Enhancing teaching effectiveness in ancient architecture colour painting through blended design - Jiaqi Yin; Adylbek Gulnaz (Architecture Image Studies Scientific Journal)
This study aimed to implement the Analysis, Design, Development, Implementation, Evaluation (ADDIE) model to enhance the effectiveness of teaching colour painting in the training of future professionals. The methodology involved analysing the current teaching state in this course at Henan Technical College of Construction, combining traditional education with applying the ADDIE model. A comparative analysis was conducted between the learning outcomes of students using the ADDIE model and those taught using traditional methods. The ADDIE model facilitated the improvement of course structure, established clear learning objectives, and developed assessment mechanisms that took into account both theoretical knowledge and practical skills. The integration of blended design led to increased student engagement and interest in the subject. The results showed significant improvement in students’ abilities, knowledge, and practical skills. Furthermore, the new approach to assessment provided more accurate information on students’ knowledge levels and progress. The findings of the research indicate the effectiveness of the proposed model for teaching similar subjects in vocational institutions. A key aspect is the adaptation of educational methods to meet the modern requirements of professional training. The study examined the impact of technological innovations on the learning process and their role in shaping students’ competencies. The use of blended teaching methods not only increased student engagement but also fostered the development of creative thinking and visual perception. An important component of the research was the design of effective educational activities that promote the development of critical thinking and student autonomy. Various methods, such as group projects and creative tasks, enabled participants to present their ideas and receive feedback. This also boosted their motivation to learn, as students were able to apply their acquired knowledge in practice. Overall, the integration of the ADDIE model not only improved the quality of instruction but also created conditions for a deeper understanding of colour painting as an artistic discipline, which is essential in the training of professionals.